2007
DOI: 10.1152/ajpheart.00471.2007
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of propagated mouse ventricular action potentials: effects of molecular heterogeneity

Abstract: The molecular heterogeneity of repolarizing currents produces significant spatial heterogeneity and/or dispersion of repolarization in many mammalian cardiac tissues. Transgenic mice are prominent experimental models for the study of the molecular basis of repolarization and arrhythmias. However, it is debated whether the small mouse heart can sustain physiologically relevant heterogeneity of repolarization. We used a comprehensive model of the mouse action potential (AP) to predict how small a region of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
2
16
0
Order By: Relevance
“…However, if  = 4 and , this distinction is quite prominent at all the values of that we have considered. For studies on transmural heterogeneity in mouse tissue, please refer to [38], [39].…”
Section: Resultsmentioning
confidence: 99%
“…However, if  = 4 and , this distinction is quite prominent at all the values of that we have considered. For studies on transmural heterogeneity in mouse tissue, please refer to [38], [39].…”
Section: Resultsmentioning
confidence: 99%
“…Computer simulations could provide a potential means to further explore the pro-arrhythmic consequences of RV/LV differences in ionic currents, particularly employing whole heart models [6063]. However, this would also entail obtaining further independent information on detailed conduction pathway morphology, including extents of fibrosis and cell–cell conductance information in Scn5a +/− hearts.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would also entail obtaining further independent information on detailed conduction pathway morphology, including extents of fibrosis and cell–cell conductance information in Scn5a +/− hearts. While groups have previously used whole heart models of WT mouse hearts [60], it has been shown previously that Scn5a +/− hearts exhibit heterogeneous fibrosis [2], along with heterogeneous expression of connexin 43 and upregulation of hypertrophic markers including β-MHC and skeletal α-actin [64]. …”
Section: Discussionmentioning
confidence: 99%
“…The one-dimensional (1D) model of mouse ventricular tissue consists of 190 cardiac cells, both for WT and TG mice. Two configurations of the tissue were simulated: a 1D cable and a ring of N ϭ 190 model cells connected end to end with gap junction conductances ggap (7). Cell length was 100 m (7, 41); therefore, the length of the cable and the ring was 19 mm, which is approximately equal to the circumference of a mouse ventricle with a diameter of 6 mm (54).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of [Ca 2ϩ ] i alternans in rodent cardiac tissues has been studied both experimentally and using computer simulations (7,14,38). Diaz et al (14) showed that pharmacological depression of RyRs with tetracaine led to alternans in rat cardiac myocytes.…”
Section: Differences In Aps and Ca 2ϩ Handling In Isolated Ventriculamentioning
confidence: 99%